2004
DOI: 10.1159/000077423
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Continuous Positive Airway Pressure Treatment on Insulin Sensitivity in Patients with Obstructive Sleep Apnoea Syndrome and Type 2 Diabetes

Abstract: Background: The obstructive sleep apnoea syndrome (OSA) is a frequent condition, as well as type 2 diabetes mellitus. Both diseases are characterized by insulin resistance. Objectives: The aim of this study was to establish whether OSA is an independent risk factor for increased insulin resistance in diabetics. For this purpose, we tested the hypothesis that the insulin sensitivity in patients with type 2 diabetes and OSA can be improved by 2 days or 3 months of continuous positive airway pressure (CPAP) treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
139
3
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(157 citation statements)
references
References 32 publications
9
139
3
6
Order By: Relevance
“…Regression analyses found that there was no relationship between the number of antidiabetes medication prescriptions and HbA 1c levels. These observations reinforce the findings of others that use of CPAP can reduce hypertension (35) and possibly reduce insulin resistance (18)(19)(20), leading to lower serum glucose levels and HbA 1c levels (21,22,36). However, this is the first time a study, based on the management of patients in actual clinical practice, has shown that use of CPAP leads to lower HbA 1c levels over five consecutive years compared with untreated patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regression analyses found that there was no relationship between the number of antidiabetes medication prescriptions and HbA 1c levels. These observations reinforce the findings of others that use of CPAP can reduce hypertension (35) and possibly reduce insulin resistance (18)(19)(20), leading to lower serum glucose levels and HbA 1c levels (21,22,36). However, this is the first time a study, based on the management of patients in actual clinical practice, has shown that use of CPAP leads to lower HbA 1c levels over five consecutive years compared with untreated patients.…”
Section: Discussionsupporting
confidence: 88%
“…The short-term effect of CPAP treatment on diabetes is controversial, with some studies reporting an improvement in insulin sensitivity (18)(19)(20) and a reduction in HbA 1c levels (21,22), while others have reported no effect (23).…”
mentioning
confidence: 99%
“…110 -112 Vascular and other adverse effects of insulin resistance may contribute to cardiovascular disease in OSA. However, although some studies suggest that CPAP therapy may reduce insulin resistance in OSA, 113 a systematic review of 24 earlier reports, while confirming a probable independent link between SDB, glucose intolerance, and insulin resistance, also concluded that studies on the treatment of SDB with CPAP yielded inconsistent results and did not reveal an improvement in the metabolic disturbance after treatment. 114 Finally, related metabolic dysregulation such as leptin resistance and the metabolic syndrome also have been linked to OSA.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…Лептин, синтезируемый главным образом под-кожно-жировой клетчаткой, имеет эффект подавления аппетита на уровне гипоталамуса, грелин же, напро-тив, имеет центральное действие, возбуждает аппе-тит и вызывает чувство голода [52,53]. Многократные исследования демонстрируют повышенный уровень циркулирующего лептина при СОАС и его снижение при режиме искусственной вентиляции легких посто-янным положительным давлением (СРАР-терапия) [54]. Следовательно, можно было бы предположить, что люди с СОАС должны иметь сниженный аппетит вплоть до пол-ного отказа от приема пищи.…”
Section: педиатрическая фармакологияunclassified